Clinical implication of pulmonary hospitalization in heart failure with preserved ejection fraction: from the TOPCAT. (16th September 2020) - Dong, Bin; He, Xin; Xue, Ruicong; Chen, Yili; Zhao, Jingjing; Zhu, Wengen; Liang, Weihao; Wu, Zexuan; Wu, Dexi; Huang, Huiling; Zhou, Yuanyuan; Dong, Yugang; et al.
Abstract: Aims: The aim of the study was to explore the risk factors and evaluate the prognostic implication of pulmonary hospitalization on heart failure (HF) with preserved ejection fraction (HFpEF). Methods and results: We performed a secondary analysis of the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist Trial (TOPCAT). A total of 1714 patients with HFpEF were analysed in our study. In the multivariate Cox proportional hazards regression analysis, history of chronic obstructive pulmonary disease (COPD), smoking, bone fracture after the age of 45, and previous HF hospitalization were identified as independent risk factors for pulmonary hospitalization. To evaluate the prognostic significance of pulmonary hospitalization, patients were categorized into five groups according to the causes of their first hospitalization. The all‐cause and cardiovascular (CV) mortality risks in these five groups were compared using time‐varying Cox proportional hazards model. Compared with patients without hospitalization during follow‐up, those with pulmonary hospitalization were associated with a 204% increase [hazard ratio (HR) 3.04, 95% confidence interval (CI) 2.07–4.47, P < 0.001] and 164% increase (HR 2.64, 95% CI 1.60–4.36, P < 0.001) in risks of all‐cause and CV mortality, respectively, while the corresponding risk increases associated with HF hospitalization were 146% (HR 2.46, 95% CI 1.74–3.48, P < 0.001) for all‐cause mortality and 186% (HR 2.86, 95% CI 1.87–4.36, P < 0.001) for CV mortality. Conclusions: Pulmonary hospitalization was associated with a significant increase in risks of all‐cause and CV mortality, which was comparable with that associated with HF hospitalization. The results suggested that pulmonary hospitalization could be another important clinical endpoint of HFpEF.